Southern African Customs Union in a post-apartheid Southern Africa : some policy considerations. - MWASE, Ngila (1994)
Discusses measures for promotion of an effective and functional integrated market. Focusses on the removal of bottlenecks in the context of the changing sub-regional political economy, including a post-apartheid South Africa; the economic liberalization, de-regulation, commercialization and privatization of national economies; and the need to co-ordinate and rationalize the activities of SACU and those of other sub-regional economic integrating organs, viz. SADC and the PTA of Eastern and Southern African States.